A Data-Based Information System for Credit Risk Management in Banking Education - Roby Romadany; Fajar Santoso; Bhenu Arthac (At Turots: Jurnal Pendidikan Islam, 2026)
This study designs, implements, and validates a high-fidelity Data‑Based Information System for Credit Risk Management (CRIS) as an educational simulation to close the mismatch between banking industry needs and current tertiary banking curricula. The purpose of the study to develop an industry‑realistic CRIS prototype that embeds event‑driven architecture, feature stores, explainable AI, and real‑time predictive analytics into classroom practice so students acquire the technical, regulatory, and decision‑making competencies required for modern credit risk management. This research uses a design‑based research (DBR) approach guided iterative prototype development.  A DBR‑driven, event‑aware CRIS simulation is an effective educational intervention to align banking education with the technical and governance demands of contemporary credit risk management.